CONFLICTS BETWEEN BIOETHICS AND NATIONAL VALUES - Sadullaevna, Atamuratova Feruza (PT. Antis International Publisher, 2024)
Background: Bioethics addresses complex moral conundrums in medicine, health, and human rights that usually run counter to national and religious values. Specific Background: These tensions are especially evident in bioethical concerns such as genetic engineering, reproductive technologies, and euthanasia since societal perspectives are influenced by long-standing cultural, religious, and social norms. Knowledge Gap: While bioethics has been extensively studied globally, less research has been done to look at how national values in particular influence bioethical decision-making, especially in specific culture contexts like Uzbek thought. This study aims to investigate the relationship between national values and bioethics, with a focus on the influence of Uzbekistan's religious and cultural beliefs. Results: The results demonstrate that bioethical quandaries arise when modern medical technology do not align with the moral, legal, and spiritual frameworks of traditional Uzbek society. Important factors to take into account include the impact of family traditions, the need of maintaining moral standards in society, and religious opposition to organ donation and euthanasia. Novelty: This study clarifies how national values impact public opinions of bioethics, particularly in cultures that prioritize community values above individual ones, by presenting the Uzbek perspective in a fresh manner. Implications: Understanding these intersections enables healthcare practitioners and governments to make bioethical decisions that uphold human rights and national values in culturally sensitive countries.